2018
DOI: 10.1002/jcp.27896
|View full text |Cite
|
Sign up to set email alerts
|

miR‐133a‐3p suppresses cell proliferation, migration, and invasion and promotes apoptosis in esophageal squamous cell carcinoma

Abstract: Objective This study aimed to investigate the expression levels of miR‐133a‐3p and collagen type I α 1 (COL1A1) in esophageal squamous cell carcinoma (ESCC) to find out the relationship between miR‐133a‐3p and COL1A1 and their influence on ESCC propagation, migration, invasion, and apoptosis. Methods The messenger RNA expression levels of miR‐133a‐3p and COL1A1 in ESCC were detected by quantitative reverse‐transcription polymerase chain reaction. The expression of COL1A1 protein was examined via western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 19 publications
(41 reference statements)
0
46
1
Order By: Relevance
“…5 Accumulating studies have indicated that miR-133a-3p serves in a tumor suppressive role in cancers. [6][7][8] For instance, Zhang et al 6 found forced miR-133a-3p expression inhibits autophagy to hinder gastric cancer metastasis via blocking GABARAPL1 and ATG13 expression. 6 In addition, Yin et al 7 showed miR-133a-3p expression level was decreased in esophageal squamous cell carcinoma, and it could negatively regulate COL1A1 expression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Accumulating studies have indicated that miR-133a-3p serves in a tumor suppressive role in cancers. [6][7][8] For instance, Zhang et al 6 found forced miR-133a-3p expression inhibits autophagy to hinder gastric cancer metastasis via blocking GABARAPL1 and ATG13 expression. 6 In addition, Yin et al 7 showed miR-133a-3p expression level was decreased in esophageal squamous cell carcinoma, and it could negatively regulate COL1A1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] For instance, Zhang et al 6 found forced miR-133a-3p expression inhibits autophagy to hinder gastric cancer metastasis via blocking GABARAPL1 and ATG13 expression. 6 In addition, Yin et al 7 showed miR-133a-3p expression level was decreased in esophageal squamous cell carcinoma, and it could negatively regulate COL1A1 expression. 7 Functional assays indicated miR-133a-3p was able to inhibit cell growth by inhibiting apoptosis via affecting COL1A1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 39 ] Previous studies have demonstrated ESCC cells could produce COL1A1 endogenously, [ 40 ] and miR-133a-3p could inhibit the ESCC cell proliferation, invasion, and migration by targeting COL1A1. [ 41 ] However, the specific roles of COL1A2 in various tumors remain controversial. In bladder and colorectal cancer, COL1A2 was significantly downregulated and mainly plays an anticarcinogenic role in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…COL1A1 and bronectin 1 (FN1) are highly expressed in esophageal squamous cell carcinoma (ESCC) tissues. Both COL1A1 and FN1 can promote ESCC cell proliferation and invasion [32,33]. COL1A2 is signi cantly down-regulated in colorectal cancer (CRC) tissues, and COL1A2 mRNA expression levels are related to tumor differentiation, invasion, and lymph node metastasis in CRC patients.…”
Section: Expression Of Lgals1 and Its Diagnostic Value In Escamentioning
confidence: 99%